Exploration of FPGA for high speed power electronic system control - Hou, Jianwen (Nanyang Technological University, 2020)
As the development of power electronics technology, the control technology of power converters is more and more important. The usual semiconductors working frequency implies the requirement of very fast sampling and control. Conventional micro-controller and digital signal processors can not complete complex control algorithms at very high speed due to the serial implementation of program. And the field programmable gate array (FGPA) can achieve the task of very high-speed computations. This dissertation uses the ARTY Z7 board designed by Xilinx as the development platform. And there is a soft core ZYNQ as the central processor used SOPC technology in the FPGA. In this project, I will analyze the whole process in software and hardware of the control system. In hardware part, this dissertation firstly introduces the overall hardware design steps, then introduces specific solutions for each functional module, including FPGA and PWM modules. PWM and ADC modules consist of using the Verilog HDL to generate interface function modules. In the software section, I will discuss the design of the entire system first, then explain in detail of the design flow of each functional module.